Linear to Digital Television: Operación Triunfo, Adapting to Social Networks and Streaming : A Paradigm Shift from Linear Television to Digital Platforms and Social Networks: Operación Triunfo, an Example of Transformation - Caffarel-Rodríguez, Barbara; Oliva Gordillo, Rita (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The aim of this study is to analyse how linear television consumption moves to social networks. The proliferation of digital platforms and the growth of networks has led to a transformation in the way in which new viewers interact. Operación Triunfo 2023 is an example that adapts to this transformation and reinvents itself as a change in the entertainment paradigm for the platform.